A conceptual model of information technology innovation implementation effectiveness in higher education - Huda, Qomarul M; Hussin, Husnayati (2013)
Research on innovation in organizations has mainly focused on adoption phase as compared to implementation phase of innovation. Implementation is the critical gateway between the decision to adopt an innovation and the routine use of the innovation. In the case of IT innovation, while the development of IT innovation is relatively controllable, the actual implementation of IT is far more difficult to control as it involves complex interactions between people, technology and environment. Often times there is resistance in using the new technology and in many circumstances, the organization has to face IT implementation failure. In the context of higher education, there has been major transformation occurring in the formal education sector partly due to the development of IT innovation, as well as the form of networking, knowledge sharing and interactive learning that IT facilitate. Nevertheless, many universities are facing a lot of challenges in implementing IT innovation successfully. Although there have been some researches on the implementation of innovations in general, very few studies explored IT innovation implementation in the context of higher education. The purpose of this paper is to propose a conceptual framework for evaluating IT innovation implementation in higher educational institutions (HEIs), particularly in the developing countries. The proposed model was derived from the general innovation models, but was adapted to suit the HEIs context.